EMPOWERING MOTHERS IN THE PROCESSING OF LOCAL CLARIAS NUGGETS DIVERIFIED FOODS INTO HEALTHY MPASI FOR STUNTING UNDER-FIVES IN THE WORKING AREA OF KASEMEN PUSKESMAS IN 2023 - Rahmawati, Dewi; Sundary Lintang, Santi; Yulidar, Elfina; Ernawati, Eka; Alifiani, Herna; Atma Sella, Marlina; Febriyanti, Rizka; Fadilah, Eli (LPPM Univ. Ibn Khaldun Bogor, 2023)
Community service in the form of health education activities for the target community through 2 activities in the form of providing education about stunting and appropriate feeding patterns for toddlers based on the contents of my plate, and the second stage is demonstrating the steps for cooking one of the fish-based complementary food menus (catfish) become a food that is often in demand by children in the form of processed